INFLUENCE OF CENTRAL ASIAN CLIMATIC CONDITIONS ON THE COMPATIBILITY OF REINFORCED CONCRETE ELEMENTS - Akhmedov Islombek; S.Kholmirzayev; Umarov Isroil; B.Sharopov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. Issues of development of the economy of Tajikistan, as well as prospects for economic development and economic development, as well as prospects for the development of the economy of Tajikistan were discussed in Dushanbe. A criminal case has been opened on this fact, an investigation is underway.